Development Of Curturally Responsive Teaching (CRT) Based On Pjok To Improve The Socio-Emotional Competence Of Elementary School Students - Evi Rahmayanti; Hermawan pamot Raharjo (Journal of Physical Education and Sports, 2026)
This study aims to develop PJOK learning tools based on Culturally Responsive Teaching (CRT) to enhance the social-emotional competencies of elementary school students in Phase A. The background of this research highlights the importance of integrating local culture into PJOK learning to create relevant and meaningful learning experiences for students, as well as the need to develop their social and emotional skills, which are still underdeveloped The research subjects were Phase A students at SDN 06 Mulyoharjo and SDN 05 Bojongbata, Pemalang Subdistrict, Pemalang Regency. This study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis stage identified the needs of both students and teachers, as well as reviewed relevant theories. This is evidenced by trial results in which the significance values for each aspect were as follows: self-awareness level = 0.177, self-management level = 0.383, social awareness level = 0.424, relationship-building skills = 0.398, and responsible decision-making = 0.358. Since all significance values are greater than 0.05, it can be concluded that there is no significant difference in the level of social-emotional competence between students at SDN 06 Mulyoharjo and SDN 05 Bojongbata. Research Conclusions: 1) Overall, this thesis concludes that the development of a CRT-based PJOK learning model is highly relevant and can serve as an alternative solution to enhance the social-emotional competence of elementary school students; At the same time, it helps preserve local cultural values that can be revitalized and reintroduced to today’s generation of children.